Outcomes of Descemet Membrane Endothelial Keratoplasty Using Cornea From Elderly Donors Aged 80 Years and Older: In the Aftermath of Current Donor Shortage. Issue 11 (3rd November 2022) - Basak, Samar K.; Basak, Soham; Gajendragadkar, Nidhi
Abstract : Purpose: The purpose of this study was to report the outcomes of Descemet membrane endothelial keratoplasty (DMEK) using corneas from elderly donors aged 80 years and older. Methods: Eighty eyes of 78 patients who underwent DMEK-only or DMEK combined with cataract extraction (triple-DMEK) with surgeon-prepared graft between April 2016 and March 2020 were reviewed. Corrected distance visual acuity, endothelial cell density (ECD), and endothelial cell loss after 6 months, 1 year, and 2 years were analyzed. Results: The mean donor age was 83.6 ± 3.7 years (range: 80–100 years), and the mean donor ECD was 2889 ± 177 cells/mm 2 (range: 2604–3460 cells/mm 2 ). The mean recipient age was 67.2 ± 6.9 years (range: 60–89 years), and the mean follow-up was 21 ± 11 months (range: 6–52 months). The mean corrected distance visual acuity improved from a preoperative value of 1.36 ± 0.67 logarithm of the minimum angle of resolution to 0.22 ± 0.18 at 6 months (n = 75), 0.21 ± 0.2 at 1 year (n = 64), and 0.23 ± 0.3 logarithm of the minimum angle of resolution at 2 years (n = 41), respectively ( P < 0.001). In 72 eyes (96%), the graft remained transparent until the last follow-up visit. The mean postoperative ECD was 2073 ±336 (n = 75), 1951 ± 379 (n = 65), and 1807 ± 431 cells/mm 2 (n = 41) at 6 months, 1 year, and 2 years, respectively. Five eyes (6.7%) had donor detachments of which 4 required rebubbling. Two grafts failed after 1 year, and 2 eyes (2.6%) had graft rejection, of which 1 eye was reverted successfully by medical management. Conclusions: Cornea from elderly donors aged 80 years and older with good selection criteria may be considered for DMEK with successful outcomes. For India and other countries with unmet tissue needs, every best single cornea counts.